Long-Term Survival Analysis of Transarterial Chemoembolization Plus Radiotherapy vs. Radiotherapy for Hepatocellular Carcinoma With Macroscopic Vascular Invasion - Su, Ting-Shi; Li, Li-Qing; Meng, Wan-Wan; Wang, Yu-Dan; Chen, Yi-Tian; Li, Jian-Xu; Du, You-Qin; Qu, Song; Zhao, Chang; Huang, De-Jia; Liang, Shi-Xiong; Li, Le-Qun (Frontiers in Oncology, 2020)
Background: Major vessel invasion (MVI) is a terminal manifestation of hepatocellular carcinoma (HCC), carries an extremely poor prognosis. In Chinese and Korean HCC guidelines, transarterial chemoembolization (TACE) or/and radiotherapy (RT) is adopted for treatment of MVI. In current study, we aimed to compare the long-term outcome of TACE+RT to RT alone in patients with local advanced HCC with MVI. Methods: In this retrospective study, 148 treatment-naive patients of HCC with MVI were enrolled. Of the patients enrolled, 49 received TACE+RT treatment, while 99 patients received RT alone as a monotherapy. Overall survival (OS), progression-free survival (PFS), and intrahepatic control were evaluated using univariable and propensity-score matched analyses. Results: During follow-up, 126 (85.1%) patients died. The median follow-up time was 55.0 months in RT group and 57.0 months in TACE+RT group. TACE+RT group showed better OS and PFS than the RT group, but intrahepatic control was comparable in these two groups. Of 41 cases well-pairs after propensity score matching, the associations between TACE+RT and better OS and PFS remained (15.0 versus 8.0 months, and 8.0 versus 4.0 months, all P<0.05). The 1-, 2-, 3-, and 5-year OS in the TACE+RT group were 56.1%%, 28.6%, 20.8%, and 15.7% versus 31.5%, 13.1%, 9.8%, and 6.7% in the RT group, respectively (P=0.017). The 6-, 12-, 24-month rates in the TACE+RT group were 51.2%, 39.0%, and 23.1% versus 36.6%, 13.9%, and 11.1% in the RT group, respectively (P=0.04). Two (4.1%) patients experienced radiation-induced liver disease (RILD) and one (2.0%) experienced RT-related GI bleed in TACE+RT groups. Nine (9.1%) patients experienced RILD and two (2.0%) experienced RT-related GI bleed in RT groups. Conclusion: TACE+RT was well complementarity with no more complications, providing a better PFS and OS compared with RT alone treatment for HCC with MVI.